Change of integration model, i.e. on the failure of a neofunctional concept of a crisis (Economic and Political Thought, 2015)
In the present article, I verify the neo-functional assumptions about thedevelopment of European integration through successive crises. I advancea thesis that changes in the integration processes carried out during thecrisis of the euro area are exceptional and they head in three directions.Firstly, it is typical of them to strengthen intergovernmentalism and politicalpower of the largest Member States. Secondly, during the crisis, formaland informal competences of the EU technocratic institutions, including theEuropean Commission and the ECB, increased. Both institutions yielded tothe political pressure from powerful governments. This has led to a reductionin the autonomy of these institutions and their stronger subordination to thedominant Member States. Thirdly, the crisis has provided an opportunity toreinforce the segmentation of Europe into the eurozone and the “secondcircle of integration”.